Abandonment of intravenous volume expansion after preoperative receipt of α-blockers in patients with adrenal pheochromocytoma was not an independent risk factor for intraoperative hemodynamic instability - Yan, Kun-wu; Tian, Xiao-fei; Wu, Yan-ni; Cai, Meng; Guo, Ming-tao (Frontiers in Endocrinology, 2023)
Background There is no consensus on whether intravenous rehydration must be added after preoperative phenoxybenzamine (PXB) administration for pheochromocytoma. The aim of this study is to investigate whether abandonment of intravenous volume expansion after PXB administration is associated with intraoperative hemodynamic instability. Methods 83 Patients with pheochromocytoma received surgical treatment in the Department of Urology, Handan First Hospital, between October 2014 and July 2022. All patients were subclassified into either the hemodynamic stability group (HS group) or the hemodynamic instability group (HU group) according to whether intraoperative hemodynamic instability occurred, with 51 cases in HS group and 32 cases in HU group. Differences in data between the two groups were examined, and the risk factors for intraoperative hemodynamic instability were analyzed using logistic regression. Results The results of the analysis showed no statistically significant differences in age, sex, location of the tumor, surgical method, body mass index (BMI) ≥ 24 kg/m2, blood and urine catecholamine test results, preoperative oral PXB followed by combined intravenous volume expansion, proportion of patients with hypertension or diabetes mellitus or coronary heart disease between the two groups (P>0.05). The size of the tumor in the HS group was smaller than that in the HU group (5.3 ± 1.9 cm vs 6.2 ± 2.4 cm P=0.010). Multivariate analyses demonstrated that abandonment of intravenous volume expansion after preoperative receipt of α-blockers in patients with adrenal pheochromocytoma was not an independent risk factor for intraoperative hemodynamic instability. Only the tumor size (P=0.025) was an independent risk factor for intraoperative hemodynamic instability. Conclusion The purpose of general preoperative intravenous fluid expansion is to prevent hypotension after the tumor has been resected. In the current study, we indicated that preoperative management of pheochromocytomas using the α-blocker PXB in combination with intravenous volume expansion does not further reduce the risk of intraoperative hemodynamic instability or postoperative complications compared with oral PXB alone. Therefore, our study supports preoperative management of pheochromocytoma with a single α-blocker, PXB, as sufficient.